Properties of Graphical-Algebraic: Exploring the Power of Graphical-Algebraic Models (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Graphical algebras are both a natural and powerful way to depict intricate dependency structures in multivariate random variables. They come in two flavours, directed or undirected, that are not mutually exclusive. However, some conditional independence structures can only be encoded in one or the other formalism. Among graphical algebras, Gaussian Graphical algebras (often referred to as GGM) are of particular interest because of their ease to be manipulated and interpreted.